De Curitiba para Moçambique: ações de educomunicação e comunicação popular - Carvalho, Guilherme (2016)
The Communication and Popular Education Center (NCEP) is a university extension program that was created in 2003 by the Department of Communication at the Federal University of Paraná (Decom/UFPR). Before producing a historical trajectory, we present in this text the results that have been achieved so far by the team and the project partners, as well as provide brief accounts of experiences. The NCEP aims to stimulate discussion on educational communication and popular communication. The undergraduate and graduate involved help the core partners in specific projects in the management of communication tools perspective. Currently, the NCEP has six partnerships in which the core members develop writing and production workshops in radio and print newspaper, as well as an international partnership with the Eduardo Mondlane University in Mozambique, which is reported in the spotlight.